2006
DOI: 10.1124/mol.105.020594
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of TWIK-Related Acid-Sensitive K+-Containing Channels to the Function of Dorsal Lateral Geniculate Thalamocortical Relay Neurons

Abstract: A genetic knockout was used to determine the specific contribution of TWIK-related acid-sensitive K ϩ (TASK)-1 channels to the function of dorsal lateral geniculate nucleus (DLG) thalamocortical relay (TC) neurons. Disruption of TASK-1 function produced an ϳ19% decrease in amplitude of the standing outward current (I SO ) and a 3 Ϯ 1-mV depolarizing shift in resting membrane potential (V rest ) of DLG neurons. We estimated that current through TASK-1 homodimers or TASK-1/TASK-3 heterodimers contribute(s) appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 36 publications
9
77
0
Order By: Relevance
“…In the current study, we examined the consequence of genetically removing TASK-3 expression on the excitability of adult CGNs. In contrast to the situation for TASK-1 knock-out (KO) neurons (Aller et al, 2005;Meuth et al, 2006), a significant depolarization of the RMP was observed in CGNs lacking TASK-3. In addition, a clear increase in the degree of AP accommodation was apparent both at threshold and suprathreshold levels of depolarization.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the current study, we examined the consequence of genetically removing TASK-3 expression on the excitability of adult CGNs. In contrast to the situation for TASK-1 knock-out (KO) neurons (Aller et al, 2005;Meuth et al, 2006), a significant depolarization of the RMP was observed in CGNs lacking TASK-3. In addition, a clear increase in the degree of AP accommodation was apparent both at threshold and suprathreshold levels of depolarization.…”
Section: Introductionmentioning
confidence: 66%
“…The increased input conductance associated with K 2P channel opening will further reduce excitability by attenuating excitatory drive (Goldstein et al, 2001;Patel and Honoré, 2001). Many neuromodulators promote closure of K 2P channels (Talley et al, 2000;Chemin et al, 2003;Heurteaux et al, 2006;Meuth et al, 2006;Mathie, 2007), and the conventional view would be that K 2P closure would increase neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been proposed that TASK channels may be involved in regulation of respiration by peripheral chemoreceptors (e.g., via hypoxic inhibition of TASK-like channels in carotid body glomus cells) (Buckler, 2007). In light of this, it is perhaps surprising that TASK knock-out mice, including the double TASK Ϫ/Ϫ mice reported here for the first time, present such an unremarkable respiratory and neurological phenotype (Aller et al, 2005;Linden et al, 2006;Meuth et al, 2006;Brickley et al, 2007). Indeed, we also tested peripheral chemosensory responses of these mice and found a significant hyperventilation in TASK Ϫ/Ϫ double knock-out mice exposed to 10% O 2 (n ϭ 5, p Ͻ 0.0005 by two-way RM-ANOVA) that was not different from that in control mice (n ϭ 6, p ϭ 0.64).…”
Section: Task Channel Contributions To Respirationmentioning
confidence: 74%
“…Expression of TASK channel transcripts is widespread throughout the CNS (Karschin et al, 2001;Talley et al, 2001;Vega-Saenz et al, 2001), and it is now clear that TASK-like background K ϩ currents contribute to regulation of excitability in numerous cell types (Millar et al, 2000;Sirois et al, 2000;Han et al, 2003;Meuth et al, 2003Meuth et al, , 2006Berg et al, 2004;Aller et al, 2005;Taverna et al, 2005;Burdakov et al, 2006;Torborg et al, 2006;Brickley et al, 2007), including many central respiratory-related neurons Washburn et al, 2002Washburn et al, , 2003. In addition, it has been proposed that TASK channels may be involved in regulation of respiration by peripheral chemoreceptors (e.g., via hypoxic inhibition of TASK-like channels in carotid body glomus cells) (Buckler, 2007).…”
Section: Task Channel Contributions To Respirationmentioning
confidence: 99%
“…We could attribute this background K ϩ current to homomeric TASK-3 channels because: 1) it was strongly inhibited by acidification but unaffected by alkalization (from pH 7.3), as expected for TASK-3 but not other TASK channels; and 2) it was potently inhibited by Zn 2ϩ at concentrations selective among TASK channels for TASK-3 homomers. These cholinergic striatal interneurons are thus distinct from other neurons studied to date, where TASK-like currents appear to represent an admixture of homomeric TASK-1 and TASK-3 as well as heteromeric TASK-1/TASK-3 channels (Berg et al 2004;Kang et al 2003;Meuth et al 2006).…”
Section: Discussionmentioning
confidence: 99%